2016
DOI: 10.1556/066.2016.45.3.8
|View full text |Cite
|
Sign up to set email alerts
|

Enhanced β-mannanase production from alternative sources by recombinant Aspergillus sojae

Abstract: β-mannanases can degrade galactomannans to mannose and it has been used in various application areas. The aim of this study was to produce the β-mannanase from carob pod extract including different nitrogen sources. The best operation values for fermentation were determined to be 8% initial sugar concentration with 0.5% yeast extract, 100 r.p.m., and 7% inoculation rate, which yielded the maximum β-mannanase activity as 423.60 U ml -1 . Effects of nitrogen sources on β-mannanase activity were also studied and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 22 publications
(14 citation statements)
references
References 23 publications
0
14
0
Order By: Relevance
“…The first condition was 8% initial substrate concentration, 147 rpm agitation speed, and 7% inoculum size; the second condition was 8% initial substrate concentration, 100 rpm agitation speed, and 7% inoculum size, which yielded to be 339.66 and 350.82 U/mL, respectively. It was also calculated that the sugar consumed, fungal growth, maximum substrate consumption rate, and maximum β‐mannanase production rate were 64.73 g/L, 14.16 g/L (gravimetrically), 8.00 g L –1 day –1 , and 29.03 g L –1 day –1 for the first and 57.51 g/L, 14.12 g/L (gravimetrically), 7.52 g L –1 day –1 , and 26.48 U mL –1 day –1 for the second, respectively . On the other hand, the effects of different nitrogen sources (pure nitrogen sources: yeast extract, beef extract, and ammonium nitrate; animal by‐products: meat bone meal, feather meal, and fish meal; and vegetable by‐products: red lentil, cotton seed meal, maize zein, and soybean meal) on β‐mannanase fermentation were also examined by Yatmaz et al, who reported that the highest β‐mannanase activities were found to be 695.6 U/mL with 0.5% of ammonium nitrate that is a pure nitrogen source, 597.31 U/mL with 0.75% of meat bone meal that is an animal by‐product, and 525.93 U/mL with 0.75% of soybean meal that is a vegetable nitrogen source .…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…The first condition was 8% initial substrate concentration, 147 rpm agitation speed, and 7% inoculum size; the second condition was 8% initial substrate concentration, 100 rpm agitation speed, and 7% inoculum size, which yielded to be 339.66 and 350.82 U/mL, respectively. It was also calculated that the sugar consumed, fungal growth, maximum substrate consumption rate, and maximum β‐mannanase production rate were 64.73 g/L, 14.16 g/L (gravimetrically), 8.00 g L –1 day –1 , and 29.03 g L –1 day –1 for the first and 57.51 g/L, 14.12 g/L (gravimetrically), 7.52 g L –1 day –1 , and 26.48 U mL –1 day –1 for the second, respectively . On the other hand, the effects of different nitrogen sources (pure nitrogen sources: yeast extract, beef extract, and ammonium nitrate; animal by‐products: meat bone meal, feather meal, and fish meal; and vegetable by‐products: red lentil, cotton seed meal, maize zein, and soybean meal) on β‐mannanase fermentation were also examined by Yatmaz et al, who reported that the highest β‐mannanase activities were found to be 695.6 U/mL with 0.5% of ammonium nitrate that is a pure nitrogen source, 597.31 U/mL with 0.75% of meat bone meal that is an animal by‐product, and 525.93 U/mL with 0.75% of soybean meal that is a vegetable nitrogen source .…”
Section: Resultsmentioning
confidence: 99%
“…Besides, it was found that the highest β‐mannanase activity reached to 482 U/mL at 6th day of fermentation, which was 1.40‐fold higher than glucose‐based medium . In another study, β‐mannanase fermentation conditions by recombinant A. sojae were also optimized by using Box–Behnken RSM in terms of initial sugar concentration, agitation speed, and inoculum size in the medium containing 0.4% (w/v) yeast extract, 0.05% MgSO 4 7H 2 O, and 0.1% K 2 HPO 4 per liter, which was reported under two optimal conditions. The first condition was 8% initial substrate concentration, 147 rpm agitation speed, and 7% inoculum size; the second condition was 8% initial substrate concentration, 100 rpm agitation speed, and 7% inoculum size, which yielded to be 339.66 and 350.82 U/mL, respectively.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations